The innate immune response elicited by Group A Streptococcus is highly variable among clinical isolates and correlates with the emm type. - Márcia Dinis; Céline Plainvert; Pavel Kovarik; Magalie Longo; Agnès Fouet; Claire Poyart (PLoS ONE)
Group A Streptococcus (GAS) infections remain a significant health care problem due to high morbidity and mortality associated with GAS diseases, along with their increasing worldwide prevalence. Macrophages play a key role in the control and clearance of GAS infections. Moreover, pro-inflammatory cytokines production and GAS persistence and invasion are related. In this study we investigated the correlation between the GAS clinical isolates genotypes, their known clinical history, and their ability to modulate innate immune response. We constituted a collection of 40 independent GAS isolates representative of the emm types currently prevalent in France and responsible for invasive (57.5%) and non-invasive (42.5%) clinical manifestations. We tested phagocytosis and survival in mouse bone marrow-derived macrophages and quantified the pro-inflammatory mediators (IL-6, TNF-α) and type I interferon (INF-β) production. Invasive emm89 isolates were more phagocytosed than their non-invasive counterparts, and emm89 isolates more than the other isolates. Regarding the survival, differences were observed depending on the isolate emm type, but not between invasive and non-invasive isolates within the same emm type. The level of inflammatory mediators produced was also emm type-dependent and mostly invasiveness status independent. Isolates of the emm1 type were able to induce the highest levels of both pro-inflammatory cytokines, whereas emm89 isolates induced the earliest production of IFN-β. Finally, even within emm types, there was a variability of the innate immune responses induced, but survival and inflammatory mediator production were not linked.